Quencher-Free Fluorescence Method for the Detection of Mercury(II) Based on Polymerase-Aided Photoinduced Electron Transfer Strategy - Haisheng Liu; Linbin Ma; Changbei Ma; Junyan Du; Meilan Wang; Kemin Wang (Sensors, 2016)
A new quencher-free Hg2+ ion assay method was developed based on polymerase-assisted photoinduced electron transfer (PIET). In this approach, a probe is designed with a mercury ion recognition sequence (MRS) that is composed of two T-rich functional areas separated by a spacer of random bases at the 3′-end, and a sequence of stacked cytosines at the 5′-end, to which a fluorescein (FAM) is attached. Upon addition of Hg2+ ions into this sensing system, the MRS folds into a hairpin structure at the 3′-end with Hg2+-mediated base pairs. In the presence of DNA polymerase, it will catalyze the extension reaction, resulting in the formation of stacked guanines, which will instantly quench the fluorescence of FAM through PIET. Under optimal conditions, the limit of detection for Hg2+ ions was estimated to be 5 nM which is higher than the US Environmental Protection Agency (EPA) standard limit. In addition, no labeling with a quencher was requiring, and the present method is fairly simple, fast and low cost. It is expected that this cost-effective fluorescence method might hold considerable potential in the detection of Hg2+ ions in real biological and environmental samples.